the Balinese Pop Song which was Semiotic Heuristic study - Ni Wayan Sariani; Rasna, I Wayan (Widya Accarya, 2020)
Abstract. This research was about Balinese pop song which was Semiotic Heuristic study. The research underlined was the fact that occurred in the Balinese popular songs as a part of the literary work featured new vocabularies as well as old vocabularies modification and also a combination of vocabularies from other languages such as Indonesian and English, considered as the "Deviate" composition from the rules of standard grammar and literary conventions. The purpose of this research was to describe the phenomenon of linguistic structure in Balinese popular song texts and the philosophical meaning of the texts Balinese popular song based on semiotic-heuristic analysis. To be able to describe these purposes, semiotic theory and structuralism were used. This research used descriptive qualitative method. The data source was derived from two texts of Balinese popular songs entitled â€œSuksma Hyang Widhiâ€ by Dek Ulikâ€ and "Bungan Sandat" by AA Made Cakra. Both of these popular songs used different styles. The song of "Bungan Sandat" mostly used words based on the rules of language and literature that was, poetic. While the song titled "Suksma Hyang Widhiâ€ mostly used a lot of ordinary words such as language used in daily life. There appeared some deviate words found out of the rules of grammar or literary conventions; however there were also words appropriately right based on the rules of language and literature, namely poetic, romantic, by symbolic and philosophical language styles. Based on the result analysis of those two songs heuristically towards the two texts of Balinese Pop songs were found the existence of violations of linguistic rules both grammatically, syntagmatically, paradigmatically, semantically and composition of these two Balinese popular songs. Keywords: the text of balinese popular song, semiotic-heuristi, philosophical meaning